Adaptive displays of body constitution in gravity cyclists - Siriski, D.; Novotny J. (Journal of Human Sport & Exercise, 2015)
The objective of our study was to investigate somatotype, body constitution and motor skills of elite cyclists of technical gravity disciplines (freestyle MTB, biketrial) and downhill gravity disciplines (fourcross, downhill) and to characterize the impact of specific training process on body constitution and level of motor skills. Test group consisted of 30 riders (15 technical gravity disciplines, 15 downhill gravity disciplines). We used Heath-Carter method to define somatotype and Matiegka method to define body constitution of cyclists. Participants attended 2 motor skills tests focused on explosive leg strength and coordination (broad jump, twist jump). Downhill gravity cyclists proved significantly higher muscle mass (downhill disciplines 47,2%, s = 3,9%; technical disciplines 44,3%, s = 3,08%; p = 0,0564) and higher value of mesomorph component (downhill disciplines 5,04, s = 0,43; technical disciplines 4,66, s = 0,69; p = 0,1103). There were no significant differences in other anthropometric values. Downhill gravity cyclists proved statistically significant differences in broad jump (downhill disciplines 226,9cm, s = 21,15cm; technical disciplines 210cm, s = 15,17cm; p = 0,042). Technical gravity cyclists proved statistically significant differencies in twist jump (technical disciplines 547,7°, s = 110,3°; downhill disciplines 441,5°, s = 65,1°; p = 0,0074). Differences in somatotype, body constitution and motoric tests relate with characteristics of training and use of specific training methods. In this study high level performance athletes were tested, therefore it could be helpful for riders and coaches to increase the efficiency of the training process.